Responting of Aloe vera L. plant to Salicylic acid and some of fertilization treatments - Abid Fulaih, Sabah Abid Fulaih; Jumaa, Farouk Faraj; Abbass, Ibraheem Salih (Journal of Kerbala for Agricultural Sciences, 2018)
The study was conducted at the field of Holticulture and Landscaping Department on (Aloe vera L.) for the duration 1/9/2012 to 1/11/2013 by adding Salicylic acid at 0, 100 and 200mg.L-1 and a combination of Humic acid at 0, 1 and 2mg.L-1 with chemical fertilizer NPK at 0 and 2.0 gm.L plant-1 to inhance the growth and leaves yield. Plants of four months old were planted on the lines inside plots. A siplit- plot with RCBD design was used. Results could be summarized as follows: The addition of Salicyalic acid significantly increased all vegetative characteristics and especially at 200 mg.L-1, which gave the highest rates of traits,the hight of plant number of leaves, leaf area,and leaf weight The fertilization by Humic acid and NPK led to a significant increasing in all traits especially the combination of 2ml. L-1 Humic acid + 2gm.plant-1 NPK (N5). The Interaction between Salicyalic acid and fertilizer (especially S2N5 treatment) gave significant increasing reached 74.87%، 33.59%،55.26 ،37.77%،75.97% and 73.92% for traits، the hight of plant ،number of leaves leaf fresh and dry weight and the weight of gel respectively.